Genetic control of traits related to phosphorus use efficiency in tropical maize - Flávia Ferreira Mendes; Lauro José Moreira Guimarães; Cláudia Teixeira Guimarães; João Cândido Souza; Paulo Evaristo Oliveira Guimarães; Sidney Netto Parentoni (Crop Breeding and Applied Biotechnology, 2015)
Knowing the inheritance of traits is essential to establish selection strategies in breeding programs. The aim of this study was to determine the genetic control of traits related to the phosphorus use efficiency in maize. A total of 280 progenies were developed according to design III, which were evaluated in the field under high and low phosphorus (P) availability. The genetic variance components were estimated for the agronomic traits and indices that define P use efficiency. The results indicated that the additive and dominance effects were important in explaining the genetic variability for the flowering time, grain yield and P efficiency indices. However, dominance effects prevailed, indicating that breeding efforts should be made to develop hybrids exploiting the heterosis for traits related to P use efficiency.